A new stag beetle of the genus Dorcus MacLeay, 1819 from Xizang, China (Coleoptera: Lucanidae: Lucaninae) - Qi, Zhi-Hao; Xin, Fei-Yi; Zhong, Xiao-Tian; Song, Hai-Tian; Liang, Guang-Hong (Zootaxa, 2026)
In the present study, a new stag beetle, namely Dorcus liangi Qi, Xin & Zhong, sp. nov. from Xizang, southwestern China is described and illustrated. The new species is very similar to D. fujiii Nagai & Maeda, 2010 and D. hei Liu, Luo & Wang, 2025 but it can be clearly distinguished from the latter two based on morphological details, especially genital characters. In addition, the genetic distance of the mitochondrial COI also supports the validity of the new species.